Unnamed soils, lost opportunities - Certini G.; Scalenghe R. (Environmental Science & Technology, 2019)
Have you ever read a scientific article about brown bear referred to as “an animal with long, thick brown fur and a shoulder height up to 150 cm” instead of using its scientific name, Ursus arctos? Or one where Oryza sativa is defined as “a plant that may grow to 1.8 m and produce pendulous inflorescences 50 cm long with edible caryopses”? Science employs as much as possible simple, stable, and widely accepted international classification systems for naming beings and things. The best known of such systems is the Linnaean system for naming organisms by two Latin terms, which refer to genus and species. Classifications are used in other fields, such as astronomy, chemistry, metallurgy, physics, and archeology.